Pengajian Majlis Ta’lim Bentuk Tanggung Jawab Masyarakat Sebagai Pendidikan Seumur Hidup: Perspektif Al-Qur’an dan Hadist - Fitria, Mita (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The recitation of majlis ta'lim is a form of community responsibility in lifelong education in the perspective of the Quran and Hadith. In the Quran, Allah Almighty invites mankind to seek knowledge and increase their knowledge. The hadiths of Prophet Muhammad (peace be upon him) also emphasize the importance of seeking knowledge as a religious commandment. Majlis ta'lim is a forum that provides opportunities for people to continue to learn and develop religious knowledge throughout life. Through the recitation of majlis ta'lim, individuals can learn the teachings of Islam, understand the Quran, the hadiths of the Prophet, and various other religious aspects. In majlis ta'lim, people can share knowledge, experience, and understanding of religion. This enables continuous and mutually enriching learning in an inclusive environment. In the perspective of the Quran and Hadisth, the recitation of majlis ta'lim can also be considered as a form of worship, because seeking knowledge is part of worship to Allah SWT. Through the study of majlis ta'lim, people can continue to improve religious understanding, strengthen creeds, improve morality, and practice Islamic teachings in daily life. Majlis ta'lim also serves as a center for the dissemination of good values and religious illumination to the public at large. In the perspective of lifelong education, majlis ta'lim recitation provides opportunities for individuals to continue learning, develop religious knowledge, and increase their spiritual awareness throughout life. This helps in forming a better person, increasing faith, and making a positive contribution to society and the nation. Thus, the recitation of majlis ta'lim can be considered as one of the forms of community responsibility in lifelong education, as it provides opportunities for religious learning to individuals in various stages of their lives, as well as strengthening their relationship with Allah Almighty and improving their morals and morality.